UPDATING THE EXIT FROM THE PROFILE AND ACADEMIC SKILLS AS A TOOL FOR CURRICULAR INNOVATION: THE CASE OF THE GEOGRAPHIC SCIENCES CAREER WITH EMPHASIS ON LAND USE PLANNING, NATIONAL UNIVERSITY, COSTA RICA - Araya-Ramírez, Iliana (2012)
Developing innovative approaches in higher education is essential to meeting the educational challenges of the Knowledge Society. Education and curriculum design competency under this approach offers advantages and disadvantages that are discussed in this paper. It focuses on the rationale for upgrading the graduate profile from professional and academic competences a tool for curriculum innovation, using as an example the Geographic Sciences degree with an emphasis on Land Use Planning offered at Costa Rica’s National University. Career Self-Assessment is the precedent that led to the profile update and plan of study. Contextualization is the key to curricular innovation, which is achieved through the participation of all those involved – students, graduates, professors and employers – who provide essential input to update the curricular offerings.